STUDY OF PREPAREDNESS FOR COVID-19 DISASTER AT THE REGIONAL GENERAL HOSPITAL (RSUD) H. ABDUL MANAN SIMATUPANG IN 2022 - Faizal Muslim; Ika Nur Saputri (JURNAL KESMAS DAN GIZI (JKG), 2022)
The Covid-19 pandemic which has hit the world over years places Indonesia at number 17 in the world with 353,340 active cases, 30,604 suspects, 4,763,252 confirmations, 4,282,847 recoveries, and 45,065 deaths (data on February 12, 2022). The number of Covid-19 treatments at H. Abdul Manan Simatupang Kisaran Regional General Hospital as a type C hospital and referral center shows fluctuating numbers, which peaked in August 2021 then sloped and increased again in January 2022. Since research on evaluation of the patient health services and hospital preparedness during the pandemic have not been widely carried out, therefore this research was carried out to see the preparedness of H. Abdul Manan Simatupang Kisaran Hospital in dealing with Covid-19 in 2022 as well as evaluating hospital services in the Covid-19 pandemic situation in accordance with WHO Hospital Readiness Checklist for Covid-19. The indicators used include Leadership and Incident Management Systems, Human Resources, Patient Clinical Management, Rapid Identification and Diagnosis, and Infection Prevention and Control. The study was conducted on 11 May-4 June 2022 through observation and document review methods, where the scoring results obtained were imputed to obtain the percentage of achievement and classification of each component. The results showed that there were 4 components with scores above 80 percent (adequate), namely Rapid Identification and Diagnosis (82 percent), Leadership and Incident Management Systems (86 percent), Human Resources (83 percent), and Infection Prevention and Control. (81 percent), while one other component is classified as moderate, namely Patient Management (75 percent).